Discrepancy of Serological and Molecular Patterns of Circulating Epstein-Barr Virus Reactivation in Primary Sjögren's Syndrome - Sanosyan, Armen; Daien, Claire; Nutz, Anaïz; Bollore, Karine; Bedin, Anne-Sophie; Morel, Jacques; Zimmermann, Valérie; Nocturne, Gaetane; Peries, Marianne; Guigue, Nicolas; Gottenberg, Jacques-Eric; Van de Perre, Philippe; et al. (Frontiers in Immunology, 2019)
Primary Sjögren's syndrome (pSS) is characterized by B cell hyperactivation, production of autoantibodies and increased risk of B cell lymphomas. Serological profile of Epstein-Barr virus (EBV) reactivation and increase EBV DNA levels in exocrine glands are observed in pSS, but whether these abnormalities are accompanied with disturbed systemic EBV control or have any association with pSS activity remains to be investigated. In this observational study, we initially explored anti-EBV antibodies and cell-free DNA in 395 samples from a cross-sectional plasma collection of pSS patients included in ASSESS French national cohort. Results were assessed in relation with disease activity. Further, to assess cell-associated EBV DNA we organized a case-control study including 20 blood samples from pSS patients followed in University Hospital Center of Montpellier. Results were compared with matched controls. Robust response against EBV early antigen (EA) was observed in pSS patients with anti-SSA/B (Sjögren’s Syndrome A and B) and anti-SSA autoantibodies compared to anti-SSA/B negatives (P < 0.0001 and P = 0.01, respectively). Increased beta-2 microglobulin, kappa and lambda light chains, and immunoglobulin G levels were more frequently observed in anti-EA seropositive pSS subjects compared to anti-EA negative subjects (P < 0.001; P = 0.001; P = 0.003, respectively). Beta-2 microglobulin was independently associated with anti-EA positivity in multivariate analysis (P < 0.001). Plasma cell-free EBV DNA and EBV cellular reservoir was not different between pSS patients and controls. We conclude that serological evidence of EBV reactivation was more frequently observed and more strongly associated with anti-SSA/B status and B cell activation markers in pSS. However, serological profile of EBV reactivation was not accompanied by molecular evidence of systemic EBV reactivation. Our data indicated that EBV infection remains efficiently controlled in the blood of pSS patients.